Effectiveness of Peer Support Programs for Newly Licensed Nurses in Reducing Turnover Rates - Sahar Nasser Alshahrani,; Jehan Safer Muteb Alotaibi,; Hessa Abdullah Alosaimi,; Hanan Hassan Jalwai Alanezi,; Manal Namer Alchibani,; Aeshah Musre Alabsi,; Ghadeer Mubark Albishi,; Modhi Ali Ahmad nasiri,; Manal Ali Ahmad nasiri,; Ashwaq Mohammed alshubaily,; Majed Homud Almutairi,; Mohammed Muawwad Mazyad Almutairi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Newly licensed nurses are critical to the sustainability of healthcare systems, yet they are disproportionately vulnerable to high turnover rates. The transition from academia to professional practice poses significant challenges, including increased stress, lack of confidence, and limited social support. These challenges contribute to burnout, dissatisfaction, and early exits from the profession. Peer support programs have emerged as a promising intervention to address these issues, providing newly licensed nurses with structured mentorship, emotional support, and professional guidance. This article explores the effectiveness of peer support programs in reducing turnover rates among newly licensed nurses. Drawing on a comprehensive review of existing literature, the study examines the outcomes of these programs and highlights their benefits, including improved job satisfaction, enhanced professional development, and higher retention rates. The findings underscore the need for healthcare organizations to prioritize peer support initiatives as a strategic approach to workforce sustainability.